Characterization and biological activity of extracts from artichoke leaves - Sampaio, C. (2019)
In the past years, western society has become more aware about its health, currently giving special attention to a healthy and balanced diet. Moreover, people are using again more natural resources in treatment or prevention of illnesses. Artichoke (Cynara cardunculus var. scolymus L.) is a traditional component of the Mediterranean diet that has been winning protagonism in current diets due to its nutritional interest and therapeutic properties. The well-known medicinal properties, which include hypolipidemic, hepatoprotective and antioxidant activities, are the main reasons why this plant is widely used as raw material by the pharmaceutical industry [1,2]. Here we report the results obtained in a chemical and biological evaluation of the leaves from an artichoke plant produced in Minho region by a company that produces aromatic and medicinal plants. Several extracts were prepared from fresh leaves mainly by infusion in water, ethanol and acetone in different conditions. The extracts obtained in water were fractionated to give an aqueous extract (AE) and an organic extract (OE). Chemical characterization, performed by 1H, 13C and 2D NMR, allowed the identification of chlorogenic acid in AE and cynaropicrin as the main component of OE. In addition to cynaropicrin, other rare sesquiterpenic lactones have also been identified in trace amounts, namely 11,13-dihydrodesacylcynaropicrin and 11,13-dihydro-8-deoxygrosheimin. Both extracts displayed in vitro antioxidant activity in the DPPH assay however, in Saccharomyces cerevisiae cells, OE protected against H2O2 while AE was pro-oxidant. Furthermore, OE was more antigenotoxic in in vitro DNA topology assay and AE was not able to protect DNA from H2O2 in human lymphocytes, assessed by the comet assay. Our results suggest that OE is more active than AE. Chemical composition and higher capacity to cross the plasma membrane may account to this difference. These biological properties valorize even more the use of artichoke in various nutraceutical, cosmetic and clinical applications.